Clinical experience with tocilizumab in the treatment of pregnant woman with severe COVID-19 - O. V. Riabokon; I. O. Kuliesh; O. O. Furyk; T. B. Matvieieva; K. V. Kalashnyk (Zaporozhye State Medical University, 2022)
The aim of the work - to present a case of positive use of tocilizumab in the treatment of pregnant woman with severe COVID-19. Materials and methods. A self-observation clinical case of severe coronavirus disease (COVID-19) in pregnant K., 40 years old, who was treated at Municipal Non-Profit Enterprise "Regional Infectious Diseases Clinical Hospital" of Zaporizhzhia Regional Council. The patient was treated in accordance with the "Protocol for the provision of medical care for the treatment of coronavirus disease (COVID-19)". Results. Our own clinical observation demonstrates the formation of severe COVID-19 in a 40-year-old pregnant woman in the second trimester of pregnancy. Combination treatment with glucocorticoids in the presence of oxygen dependence on the 11th day of the disease was ineffective for two days of clinical and laboratory parameters monitoring, which required a decision on the additional appointment of tocilizumab. The development of "cytokine storm" clinical and laboratory signs on the 12th day of the disease was evidenced by the preservation of fever in the range of 37.5-37.8 °C, no regression of oxygen dependence. According to laboratory data, an increase in the severity of lymphopenia as a relative quantity - up to 5 % and absolute quantity - up to 0.5 × 109/l, an increase in fibrinogen - up to 5.8 g/l and D-dimer - up to 1.9 ng/ml, high level of C-reactive protein - up to 190 mg/l. These data justify the additional use of tocilizumab, which was administered at a dose of 8 mg/kg in the absence of contraindications. Tocilizumab administration was effective, contributing to oxygen dependence regression and recovery of laboratory parameters within a week. Conclusions. Our own clinical observation demonstrates the formation of severe COVID-19 in pregnant woman in the second trimester of pregnancy. Due to the ineffectiveness of glucocorticosteroid therapy and the presence of clear clinical and laboratory signs of "cytokine storm" on the 12th day of the disease, the use of tocilizumab was effective, which contributed to the oxygen dependence regression and recovery of laboratory parameters within a week. Treatment of pregnant woman with severe COVID-19 requires adherence to existing protocols.